What Makes Us More Egocentric in Communication? The Role of Referent Features and Individual Differences. Issue 1 (2nd January 2018) - Dębska, Agnieszka; Rączaszek-Leonardi, Joanna
Abstract : The perspective-adjustment model of language interpretation assumes an initial egocentric stage in comprehension that is only later adjusted to the interlocutor's perspective. Moreover, substantial processing resources are involved in perspective-taking. However, many experiments in the perspective-adjustment framework do not control for visual salience and semantic typicality of referents. We conducted a referential task experiment focusing on salience and typicality as potential factors that may increase the cognitive costs of an interpretation. We additionally manipulated the interactive versus non-interactive nature of the task (with or without an interlocutor) to test the effects of perspective-taking on interpretation. Saliency and typicality of referents influenced the interpretation process when they were in conflict with the perspective-taking factor. Also, the interactive situations were more cognitively demanding than the non-interactive ones. These results are consistent with the constraint-based model that views interpretation as a probabilistic process of competition between constraints.